Do persons with disabilities act (2008) and organizational culture influence managerial intention to hire persons with disabilities?: The Malaysian Perspective - Magdalene C.H. Ang (Penerbit Universiti Kebangsaan Malaysia, 2014)
People generally tend to perceive persons with disabilities (PWDs) as “risky hires,” thus denying PWDs jobs for which they are qualified and capable of doing. Reasons for discrimination against PWDs are numerous, ranging from a lack of understanding of disability to an absence of effective policies and legislations to protect PWDs’ employment rights. It has been over 6 years since the Malaysian Persons with Disabilities Act (PWDA 2008) was enacted. Whether this Act has the intended impact on hiring decisions for Malaysians with disabilities has yet to be empirically ascertained. In addition, no known research exists concerning the type of organizational culture that is more supportive of disabled job applicants. Hence, the present study explores how these two factors might influence managerial intention to hire PWDs. Using a survey questionnaire, data were obtained from 201 non-disabled employers from various organizations in Sabah and Labuan, Malaysia. As hypothesized, the PWDA (2008) and organizational culture significantly predict the intention to hire PWDs. The findings hold important implications for policy makers and interest groups.